2015
DOI: 10.1002/cjce.22196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Coalescence and Breakage Kernels in Vertical Gas‐Liquid Flow

Abstract: The evolution of the bubble size distribution is an important consideration in vertical gas-liquid flow especially in determining the appropriate mass, momentum and heat transfer between two phases.In order to adequately capture the distribution and to account for its effect on the local hydrodynamics, which generally represents the dominant flow characteristic in such practical system, a numerical assessment has been performed to understand the six widely adopted different bubble coalescence and bubble breaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…For the superficial gas velocity highlighted here (UG = 0.02 m/s), the coalescence kernel (that of Luo [41]) is driven by the collision frequency (w c in Equation (28)), this is, in regions where ε is non-negligible the frequency of bubble coalescence is more predominant than the collision efficiency (P c ), which is proportional to the mean turbulent velocity as seen in Equation (31). A similar observation was made by Deju et al [59], who studied different combination of coalescence and breakup kernels in a circular rather than square bubble column. In their study, they found that the collision frequency diminishes when the eddy dissipation rate becomes insignificant at the centre of the bubble column, while the opposite occurs in respect to the collision efficiency: both calculations incorporated the model proposed by Prince and Blanch [85] for the coalescence kernel.…”
Section: Influence Of the Air Superficial Gas Velocity At Inlet On Thmentioning
confidence: 52%
See 1 more Smart Citation
“…For the superficial gas velocity highlighted here (UG = 0.02 m/s), the coalescence kernel (that of Luo [41]) is driven by the collision frequency (w c in Equation (28)), this is, in regions where ε is non-negligible the frequency of bubble coalescence is more predominant than the collision efficiency (P c ), which is proportional to the mean turbulent velocity as seen in Equation (31). A similar observation was made by Deju et al [59], who studied different combination of coalescence and breakup kernels in a circular rather than square bubble column. In their study, they found that the collision frequency diminishes when the eddy dissipation rate becomes insignificant at the centre of the bubble column, while the opposite occurs in respect to the collision efficiency: both calculations incorporated the model proposed by Prince and Blanch [85] for the coalescence kernel.…”
Section: Influence Of the Air Superficial Gas Velocity At Inlet On Thmentioning
confidence: 52%
“…For the breakage kernel a i , we use that suggested by Luo and Svendesson [40], which has been widely applied before [13,23,[59][60][61], and which calculates simultaneously the daughter distribution (b i ) according to the following prescription:…”
Section: Population Balance Model (Pbm)mentioning
confidence: 99%
“…Liquid density is one of the main factors involved in calculating the bubble interactions at the PBM, thus the non-uniformity of density in the flow domain may reflect on the values of the coalescence and break-up rates as well. Regarding the assessment works of Deju et al, [50][51][52] Cheung et al 53 and Vahaji et al, 54 the performance of many proposed bubble-interaction kernels have been investigated and assessed; however, so far no any combination of them has been specially recommended for a simulation of sub-cooled boiling flow. It is advisable that the effects from using different coalescence and break-up kernels together with this realistic sub-cooled liquid, which directly influences the bubble size calculation, will be investigated further in order to enhance the current prediction accuracy.…”
Section: Comparisons With Lee's Experimental Datamentioning
confidence: 99%
“…More recently, Deju et al (2015) conducted numerical experiments varying the combination of breakup and coalescence models, with a total of seven distinct combinations. The authors found good agreement between simulations and experimental data with regards to the interfacial area concentration and gas velocity profile predictions.…”
Section: Introductionmentioning
confidence: 99%